Minimally Invasive Image-Guided Gut Transport Function Measurement Probe - Otuya, David O.; Gavgiotaki, Evangelia; Carlson, Camella J.; Shi, Serena Q.; Lee, Ariel J.; Krall, Alexander A.; Chung, Anita; Grant, Catriona G.; Bhat, Nitasha M.; Choy, Peter; Giddings, Sarah L.; Gardecki, Joseph A.; et al. (Frontiers in Physics, 2021)
Introduction: Diseases such as celiac disease, environmental enteric dysfunction, infectious gastroenteritis, type II diabetes and inflammatory bowel disease are associated with increased gut permeability. Dual sugar absorption tests, such as the lactulose to rhamnose ratio (L:R) test, are the current standard for measuring gut permeability. Although easy to administer in adults, the L:R test has a number of drawbacks. These include an inability to assess for spatial heterogeneity in gut permeability that may distinguish different disease severity or pathology, additional sample collection for immunoassays, and challenges in carrying out the test in certain populations such as infants and small children. Here, we demonstrate a minimally invasive probe for real-time localized gut permeability evaluation through gut potential difference (GPD) measurement. Materials and Methods: The probe has an outer diameter of 1.2 mm diameter and can be deployed in the gut of unsedated subjects via a transnasal introduction tube (TNIT) that is akin to an intestinal feeding tube. The GPD probe consists of an Ag/AgCl electrode, an optical probe and a perfusion channel all housed within a transparent sheath. Lactated Ringer’s (LR) solution is pumped through the perfusion channel to provide ionic contact between the electrodes and the gut lining. The optical probe captures non-scanning (M-mode) OCT images to confirm electrode contact with the gut lining. A separate skin patch probe is placed over an abraded skin area to provide reference for the GPD measurements. Swine studies were conducted to validate the GPD probe. GPD in the duodenum was modulated by perfusing 45 ml of 45 mM glucose. Results: GPD values of -12±4 mV were measured in the duodenum across 4 swine studies. The change in GPD in the duodenum with the addition of glucose was -10±2.4 mV (p<0.001). M-mode OCT images provided electrode-tissue contact information, which was vital in ascertaining the probe’s proximity to the gut mucosa. Conclusion: We developed and demonstrated a minimally invasive method for investigating gastrointestinal permeability consisting of an image guided GPD probe that can be used in unsedated subjects.